Tingkat Kepatuhan Pasien Rawat Jalan Terhadap Penggunaan Sendok Takar Obat Di Poli Manajemen Terpadu Balita Sakit (Mtbs) UPTD Puskesmas Meureubo Kabupaten Aceh Barat: Tingkat Kepatuhan Pasien Rawat Jalan Terhadap Penggunaan Sendok Takar Obat Di Poli Manajemen Terpadu Balita Sakit (Mtbs) UPTD Puskesmas Meureubo Kabupaten Aceh Barat - Sari, Amelia; Burdah, Burdah; Rizka, Tia; Aroni, Defri; Irwani, Maria; Halimatussakdiah, Halimatussakdiah; Munazar, Munazar (JURNAL ILMIAH FARMASI SIMPLISIA, 2024)
Medicine measuring spoon is one of the measuring tools used to obtain the appropriate dose when taking medicine in liquid form so that it is effective against disease. Patient treatment compliance with the use of measuring spoons is very important for the patient's recovery in treatment. This study aims to determine the level of compliance of outpatients with the use of measuring spoons. Sampling in this study was conducted using purposive sampling method. Measurement of the level of compliance was carried out using the MMAS-8 (Eight Item Modified Morisky Adherence Scale) questionnaire by collecting data on 66 respondents. The results of this study indicate that patients with a low level of compliance with a percentage of 62.1%, a moderate level of compliance with a percentage of 24.2%, and high compliance with a percentage of 13.6%. It can be concluded that the level of compliance of outpatients with the use of measuring spoons of medicine at the Integrated Management of Sick Toddlers (IMCI) Poli UPTD Puskesmas Meureubo West Aceh Regency is in the low category.